مكانة المستهلك في ظل قانون المنافسة الجزاىري - مسعد, جلال (University of Eloued جامعة الوادي, 2020)
يضمن المستهلك وظيفة الطلب من الناحية الاقتصادية. يؤكد القانون على أن المستهلك يستفيد بشكل غير مباشر من سياسة تنافسية فعّالة و لبيان مكانة المستهلك في قانون المنافسة يقتضي الأمر، بيان الأضرار الناجمة عن عدم احترام قواعد قانون المنافسة التي هو ضحية لها، حيث ينبغي الإشارة إلى أن قانون المنافسة الجزائري، بعد تعديله، بدأ يأخذ منعرجا ساعيا نحو حماية القدرة الشرائية للمستهلك باعتباره المستفيد النهائي من النظام القانوني التنافسي . The consumer ensures the demand function in economic terms. The law affirms that the consumer benefitsindirectly from an effective competitive policy. In order to demonstrate the protection enjoyed by the consumer through the application of competition law it is necessary to mention that he suffers damage caused by the non-respect of these rules. Where it should be noted that the Algerian competition law after its amendment began to winding in order to protect the purchasing power of the consumer as the ultimate beneficiary of the competition legal system.
مجلد11، عدد3
Keywords: الحماية ; المستهلك ; الممارسات المقيدة للمنافسة ; قانون المنافسة; protection ; consumer ; anticompetitive practices ; competion low